Surface Enhanced Raman Spectroscopy of methylene blue deposited on Ag nanostructured substrates prepared by pulsed laser deposition. (January 2023) - Morales-Méndez, J.G.; Macías-Ayala, B.A.; Aguilar-Cardoso, A.A.; Limas-González, J.G.; Escobar-Alarcón, L.; Picquart, M.; Haro-Poniatowski, E.
Abstract: Pulsed laser deposition has proven to be a suitable technique to fabricate nanostructures of noble metals with different sizes and morphologies on glass substrates. Generally, this is done by varying the number of laser pulses impinging on the target. However, it is well known that the produced plasma plume has an inhomogeneous angular distribution and the quantity/density of material deposited on the substrate is higher in the center than in the periphery. Actually, a noble metal (silver in the present case, gold or copper) density gradient starting with a continuous region in its center and progressively evolving to complicate nanostructures and finally to spherical nanoparticles is obtained. Taking advantage of this morphological variation, drops of highly diluted methylene blue were deposited radially. Furthermore, TEM grids were placed in the same way. This technique gives the possibility of directly correlate the SERS signal, the underlying noble metal morphology and the optical absorption in very similar regions. In the present work we develop this method and discuss the obtained results. Highlights: An easy and straightforward method for characterizing the MB SERS signal on a nanostructured Ag substrate is presented. A nanostructured silver gradient spot was deposited by the PLD technique with MB drops distributed radially from the center. A maximum SERS signal was obtained for a quasipercolated Ag nanostructures.